The effect of porosity on thermal conductivity of the porous NiTi SMA fabricated by SHS - Kaya, Mehmet; Bugutekin, Abdulcelil; Orhan, Nuri (Natl Inst Optoelectronics, 2010)
In this study, porous NiTi shape memory aslloy (SMA) was obtained by self-propagating high-temperature synthesis (SHS) of compacts prepared from elemental nickel and titanium powders and the effect of the porosity on the pore morphologies, microstructures and thermal conductivity of products synthesised after different cold compaction pressed was examined. The porosity in the synthesised products was in the range of 55.6-59.2 vol.%, with the green porosity being the primary source of final porosity. Green porosity (in other words cold compaction pressure) was found to have an effect on porosity, pore morphology of the synthesised products. Also, it was found that the thermal conductivity of the synthesised products increased with decreasing porosity.
Keywords: Porous NiTi; Thermal conductivity; Fourier law; Shape memory alloy